Predictive value of combining urinary N-acetyl-β-D-glucosaminidase and serum homocysteine for contrast-induced nephropathy in patients after percutaneous coronary intervention - Zhai, Yiling; Luo, Changjun; Qin, Nianying; Cao, Hongying; Dong, Chunyang; Huang, Zhou; Huang, Dongling; Wang, Fan; Wei, Wanxia; Li, Jincheng; Yang, Jie; Lu, Xueling; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background: Contrast-induced nephropathy (CIN) can lead to serious complications following percutaneous coronary intervention (PCI). Urine N-Acetyl-β-D-glucosaminidase (uNAG) and serum homocysteine (sHCY) both are potential predictors for the CIN detection, but their combinations have not been explored. We aimed to combine uNAG and sHCY as predictors for the early detection of CIN and for prognosis prediction in patients after PCI. Methods: A total of two hundred and thirty-two consecutive patients undergoing PCI at a university hospital were recruited for this study. We assessed the use of individual biomarkers (uNAG and sHCY) measured around PCI and their combinations for CIN detection and prognosis prediction. Receiver operating characteristic curves (ROC) and area under the curve (AUC) were used to evaluate the predictive efficiency of potential predictors. Results: Fifty-four (23.28%) patients developed CIN. Concentrations of uNAG and sHCY increased significantly in CIN subjects (p ＜.05) than non-CIN. CIN could be predicted by uNAG and sHCY while not by creatinine at an early stage. At pre-PCI, 0, 12, 24, and 48 hours after PCI, the AUC-ROC value of uNAG in calculating total CIN were 0.594, 0.603, 0.685, 0.657 and 0.648, respectively, the AUC-ROC value of sHCY in calculating total CIN were 0.685, 0.726, 0.771, 0.755 and 0.821, respectively. The panel of uNAG plus sHCY detected CIN with significantly higher accuracy than either individual biomarker alone and earlier than sCr. For detecting total CIN, this panel yielded AUC-ROCs of 0.693, 0.754, 0.826, 0.796 and 0.844 at pre-PCI, 0, 12, 24, and 48 hours after PCI, respectively, which were superior to those of the individual biomarkers. For predicting the incidence of major adverse cardiovascular events (MACE) within 30 days to 12 months, the AUC-ROC values for uNAG and sHCY measured before discharge were 0.637 and 0.826, respectively. The combined panel yielded an AUC-ROC of 0.832. Conclusions: The uNAG and sHCY demonstrated better sensitivety and specificity for predicting the diagnosis and prognosis of CIN in patients after PCI. The combination of these biomarkers revealed a significantly superior discriminative performance for CIN detection and prognosis compared to using uNAG or sHCY alone.